Flexibility and muscular force of the lower members in elderly people practicing hydrogymnastics - Oliveira, Daniel Vicentini (2017)
Flexibility and muscular force of the lower body members of elderly people who practice hydrogymnastics in Sarandi PR Brazil, are assessed. Thirty-one elderly people were evaluated. Flexibility was assessed by the Sit and Reach test, while the muscular force of the lower members was evaluated by the Sit and Raise the Chair in 30 seconds. Data analysis was done by descriptive and inferential statistics.